A3_6 Flying Squirrels: Falling at Terminal Velocity - Dickens, Cameron; Healings, Jack; Sampson, Elliot; Carlisle, Ben (Physics Special Topics, 2020)
This paper discusses the physics behind humans landing a fall at terminal velocity. We find that there would have to be a severe increase in human size in order to survive. A 90 kg human would have to have to be 2.0 m wide and 8.5 m tall with an area of 17 m2 to survive such a fall. We also find that the fluid density would have to be 30 kgm−3 to alternatively slow the terminal velocity to survive.